GROWTH AND PRODUCTION OF SYNTHETIC MAIZE MUTANTS (M3) AT DIFFERENT WATER AVAILABILITY LEVELS - Ifayanti Ridwan; Muh. Farid Bdr (Universitas Sembilanbelas November Kolaka, 2018)
Drought causes hampered nutrient absorption and water uptake in plants hence abnormal growth and lower yield. One of alternative solutions is the development of maize varieties tolerant to drought stress through plant breeding. This study aims to find superior M3 mutant genotypes of maize that can adapt to dry land with high productivity. The study was conducted in green house of the Faculty of Agriculture, Universitas Hasanuddin using Split Plot Design. Water availability level was set as main plot consisted of 60%, 80% and 100% and maize mutant was set as subplot consisted of four M3 mutants, namely Bisma 100 gy, Bisma 200 gy, Lamuru 100 gy, and Lamuru 200 gy. In addition two varieties were used as controls ie. Bisma, and Lamuru resulted in total of 6 genotypes tested in the study. Mutant genotype of Bisma 200 gy showed tolerance to all water availability levels and significantly differed to other mutants including its parents indicated with higher yield. 100% water availability condition resulted in higher production than the other two water availability conditions with the average yield produced was 44.1 g per plant